11β-Hydroxysteroid dehydrogenase type 1 and bone - Cooper, M. S. (Osteologie, 2016)
Intracellular enzymatic metabolism of glucocorticoids is an important contributor to glucocorticoid action. The most extensively studied glucocorticoid metabolising enzymes are the 11β-hydroxysteroid dehydrogenases (11β-HSDs). These enzymes interconvert hormonally inactive glucocorticoids such as cortisone and dehydrocorticosterone with their active counterparts cortisol and corticosterone. 11β-HSDs have been reported to be expressed in bone and bone cells. This article reviews the literature relating to the expression, activity and functional consequences of 11β-HSD expression in bone. This activity appears to have clinical consequences in terms of predisposition towards osteoporosis and fracture and in the variation between individuals in the sensitivity of bone to therapeutic glucocorticoids. The existence of this enzyme system within bone opens up opportunities for new treatments to protect bone from the adverse effects of glucocorticoids.
Keywords: Bone; osteoblasts; cortisol; 11beta-hydroxysteroid dehydrogenase